1985
DOI: 10.3168/jds.s0022-0302(85)80962-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Transmitting Ability of Heifers from Genetic Evaluations of Dams When Dams and Herdmates Are Required to Have a First Record

Abstract: Estimated transmitting ability for milk production calculated from only first lactation records was regressed on miik proofs of the sire and maternal grandsire and either estimated transmitting ability of the dam calculated from only first lactations or estimated transmitting ability of the dam calculated from all lactations of a data set in which all cows were required to have milk records of first lactation. Records of 222,576 Holstein heifers in the northeastern United States were analyzed. Partial regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many reports have suggested that dam information does not predict son or daughter genetic value as well as theoretically possible (2,4,5,6,9,10,12,17,18). Evaluations for dams that include other than first lactation records have produced regressions for offspring on dams that are much smaller than genetic theory predicts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have suggested that dam information does not predict son or daughter genetic value as well as theoretically possible (2,4,5,6,9,10,12,17,18). Evaluations for dams that include other than first lactation records have produced regressions for offspring on dams that are much smaller than genetic theory predicts.…”
Section: Introductionmentioning
confidence: 99%
“…Regression coefficients associated with mixed model evaluations utilizing relationships are somewhat difficult to compare with theoretical regression coefficients because information used to evaluate one relative is also used to evaluate other relatives (11,18). Westell and Van Vleck (17,18) summarized studies using Northeast AI sire comparisons (NEAISC) and intraherd cow evaluations (1,7) in the Northeast (NE ETA). Similar studies have been done with USDA evaluations (2,3,4,5,9,10,12).…”
Section: Introductionmentioning
confidence: 99%